Highly stereocontrolled total synthesis of racemic codonopsinol B through isoxazolidine-4,5-diol vinylation - Ďurina, Lukáš; Ďurinová, Anna; Trejtnar, František; Janotka, Ľuboš; Messingerová, Lucia; Doháňošová, Jana; Moncol, Ján; Fischer, Róbert (Beilstein Journal of Organic Chemistry, 2021)
A new highly diastereoselective synthesis of the polyhydroxylated pyrrolidine alkaloid (±)-codonopsinol B and its N-nor-methyl analogue, starting from achiral materials, is presented. The strategy relies on the trans-stereoselective epoxidation of 2,3-dihydroisoxazole with in situ-generated DMDO, the syn-selective α-chelation-controlled addition of vinyl-MgBr/CeCl3 to the isoxazolidine-4,5-diol intermediate, and the substrate-directed epoxidation of the terminal double bond of the corresponding γ-amino-α,β-diol with aqueous hydrogen peroxide catalyzed by phosphotungstic heteropoly acid. Each of the key reactions proceeded with an excellent diastereoselectivity (dr > 95:5). (±)-Codonopsinol B was prepared in 10 steps with overall 8.4% yield. The antiproliferative effect of (±)-codonopsinol B and its N-nor-methyl analogue was evaluated using several cell line models.
Keywords: alkaloids; antiproliferative effect; codonopsinol B; diastereoselectivity; pyrrolidines

(untitled) - Wakana, D.; Kawahara, N.; Goda, Y. (Chem. Pharm. Bull., 2013)

(untitled) - Tsou, E.-L.; Chen, S.-Y.; Yang, M.-H.; Wang, S.-C.; Cheng, T.-R. R.; Cheng, W.-C. (Bioorg. Med. Chem., 2008)

(untitled) - Shibano, M.; Tsukamoto, D.; Masuda, A.; Tanaka, Y.; Kusano, G. (Chem. Pharm. Bull., 2001)

(untitled) - Yu, C.-Y.; Huang, M.-H. (Org. Lett., 2006)

(untitled) - Jagadeesh, Y.; Reddy, J. S.; Rao, B. V.; Swarnalatha, J. L. (Tetrahedron, 2010)

(untitled) - Oliveira, D. F.; Severino, E. A.; Correia, C. R. D. (Tetrahedron Lett., 1999)

(untitled) - Jain, V. K. (Synthesis, 2019)

(untitled) - He, J.-Y.; Ma, N.; Zhu, S.; Komatsu, K.; Li, Z.-Y.; Fu, W.-M. (J. Nat. Med., 2015)

(untitled) - Gao, S.-M.; Liu, J.-S.; Wang, M.; Cao, T.-T.; Qi, Y.-D.; Zhang, B.-G.; Sun, X.-B.; Liu, H.-T.; Xiao, P.-G. (J. Ethnopharmacol., 2018)

(untitled) - Xin, T.; Zhang, F.; Jiang, Q.; Chen, C.; Huang, D.; Li, Y.; Shen, W.; Jin, Y.; Sui, G. (Int. J. Biol. Macromol., 2012)

(untitled) - Zhang, Y.-y.; Zhang, Y.-m.; Xu, H.-y. (Int. J. Polym. Sci., 2019)

(untitled) - He, W.; Tao, W.; Zhang, F.; Jie, Q.; He, Y.; Zhu, W.; Tan, J.; Shen, W.; Li, L.; Yang, Y.; Cheng, H.; Sun, D. (J. Cell. Mol. Med., 2020)

(untitled) - Bailly, C. (Nat. Prod. Bioprospect., 2021)

(untitled) - Dikošová, L.; Otočková, B.; Malatinský, T.; Doháňošová, J.; Kopáčová, M.; Ďurinová, A.; Smutná, L.; Trejtnar, F.; Fischer, R. (RSC Adv., 2021)

(untitled) - Záborský, O.; Malatinský, T.; Marek, J.; Moncol, J.; Fischer, R. (Eur. J. Org. Chem., 2016)

(untitled) - Záborský, O.; Štadániová, R.; Doháňošová, J.; Moncol, J.; Fischer, R. (Synthesis, 2017)

(untitled) - Ďurina, L.; Malatinský, T.; Moncol, J.; Záborský, O.; Fischer, R. (Synthesis, 2021)

(untitled) - Lai, J.; Sayalero, S.; Ferrali, A.; Osorio-Planes, L.; Bravo, F.; Rodríguez-Escrich, C.; Pericàs, M. A. (Adv. Synth. Catal., 2018)

(untitled) - Dou, Q.-Y.; Tu, Y.-Q.; Zhang, Y.; Tian, J.-M.; Zhang, F.-M.; Wang, S.-H. (Adv. Synth. Catal., 2016)

(untitled) - Chen, Y. K.; Yoshida, M.; MacMillan, D. W. C. (J. Am. Chem. Soc., 2006)

(untitled) - Juarez-Garcia, M. E.; Yu, S.; Bode, J. W. (Tetrahedron, 2010)

(untitled) - Enders, D.; Wang, C.; Liebich, J. X. (Chem. – Eur. J., 2009)

(untitled) - Ibrahem, I.; Rios, R.; Vesely, J.; Zhao, G.-L.; Córdova, A. (Synthesis, 2008)

(untitled) - Xu, F.-F.; Chen, L.-Y.; Sun, P.; Lv, Y.; Zhang, Y.-X.; Li, J.-Y.; Yin, X.; Li, Y. (Chirality, 2020)

(untitled) - Záborský, O.; Šoral, M.; Fischer, R. (Tetrahedron Lett., 2015)

(untitled) - Miyabe, H.; Moriyama, K.; Takemoto, Y. (Chem. Pharm. Bull., 2011)

(untitled) - Hoveyda, A. H.; Evans, D. A.; Fu, G. C. (Chem. Rev., 1993)

(untitled) - Gil, L.; Compère, D.; Guilloteau-Bertin, B.; Chiaroni, A.; Marazano, C. (Synthesis, 2000)

(untitled) - Kuznetsova, L. I.; Maksimovskaya, R. I.; Fedotov, M. A. (Russ. Chem. Bull., 1985)

(untitled) - Oguchi, T.; Sakata, Y.; Takeuchi, N.; Kaneda, K.; Ishii, Y.; Ogawa, M. (Chem. Lett., 1989)

(untitled) - Yamada, Y. M. A.; Ichinohe, M.; Takahashi, H.; Ikegami, S. (Org. Lett., 2001)

(untitled) - Prat, D.; Delpech, B.; Lett, R. (Tetrahedron Lett., 1986)

(untitled) - Bartlett, P. A.; Jernstedt, K. K. (J. Am. Chem. Soc., 1977)

(untitled) - Mihelich, E. D.; Daniels, K.; Eickhoff, D. J. (J. Am. Chem. Soc., 1981)

(untitled) - Surivet, J.-P.; Goré, J.; Vatèle, J.-M. (Tetrahedron Lett., 1996)

(untitled) - Roush, W. R.; Michaelides, M. R. (Tetrahedron Lett., 1986)

(untitled) - Nakata, M.; Tamai, T.; Kamio, T.; Kinoshita, M.; Tatsuta, K. (Bull. Chem. Soc. Jpn., 1994)

(untitled) - Takahata, H.; Banba, Y.; Momose, T. (Tetrahedron, 1991)

(untitled) - Fiaux, H.; Popowycz, F.; Favre, S.; Schütz, C.; Vogel, P.; Gerber-Lemaire, S.; Juillerat-Jeanneret, L. (J. Med. Chem., 2005)